Applications of Social Media Mining and Skyline Processing on Travel Recommendation Systems a Survey - Verma, Uttra Kumar; Minj, Jasmine (International Journal of Computer Sciences and Engineering, 2025)
When arranging an excursion, clients dependably have particular inclinations with respect to their travels. Rather than confining clients to constrained inquiry alternatives, for example, areas, exercises, or eras, we consider self-assertive portrayals as catchphrases about customized necessities. This paper discusses travel recommendation techniques which help a user in finding tourist locations that he/she might like to visit a place from available user-contributed information and photos of that place available on sharing websites. This paper describes methods used to mine demographic information and provide travel recommendation to users. This paper also discusses skyline query processing.